1993
DOI: 10.1021/ja00070a069
|View full text |Cite
|
Sign up to set email alerts
|

[Mn(III)(2-OHsalpn)]2 is an efficient functional model for the manganese catalases

Abstract: Manganese catalases use a dinuclear active site to catalyze the disproportionation of hydrogen peroxide to dioxygen and water. A low-resolution structureof the Thermus thermophilus enzyme demonstrates that two manganese ions are in close proximity (~3 . 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 0 publications
5
79
0
3
Order By: Relevance
“…The minimization yielded two stable structures with an energetic gap of 44.9 kJ·mol -1 in favor of the mesocate conformation. For both conformers in these theoretical structures (taken as isolated molecule in the gas phase), the angle formed by the phenyl groups of the ligands is quite wide in comparison with the manganese complex just mentioned, [16] but a search in the Cambridge Crystallographic Database shows that the very flexible salen-type ligand can be very distorted by packing constraints in condensed phase. It is then reasonable to propose that the present dinuclear lanthanide() complexes adopt preferentially a mesocate form, with the ligands in the hairpin conformation.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The minimization yielded two stable structures with an energetic gap of 44.9 kJ·mol -1 in favor of the mesocate conformation. For both conformers in these theoretical structures (taken as isolated molecule in the gas phase), the angle formed by the phenyl groups of the ligands is quite wide in comparison with the manganese complex just mentioned, [16] but a search in the Cambridge Crystallographic Database shows that the very flexible salen-type ligand can be very distorted by packing constraints in condensed phase. It is then reasonable to propose that the present dinuclear lanthanide() complexes adopt preferentially a mesocate form, with the ligands in the hairpin conformation.…”
Section: Resultsmentioning
confidence: 90%
“…In the case of lanthanides, helicates mainly possess a three-stranded helicate Ln 2 L 3 structure (in such case, the two lanthanide ions are wrapped by three ligands), while mesocate complexes of the type M 2 L 2 -schematically shown in Figure 1, b -are common for both d and f elements. [13] For instance, Gelasco and Pecoraro described the crystal structure of a closely related dimeric manganese() complex of the Schiff base 1,3-bis(5-nitrosalicylidenimino)-2-propanol: [16] this dimeric manganese complex has a µ 2 -alkoxy core with a symmetric envi-ronment for the manganese() ions. The authors showed that the ligands adopt a hairpin conformation and that two of them wrap the two metallic ions in an antiparallel mode to form the neutral mesocate Mn 2 L 2 complex as schematically drawn in Figure 1, b.…”
Section: Resultsmentioning
confidence: 99%
“…Catalase Activity-Although the catalase activity of 2,3-HPCD is unprecedented for a non-heme mononuclear Fe(II) enzyme, it is a commonly encountered reaction for heme containing enzymes and proteins including the large family of prototypical catalases (45,46), as well as for catalases containing a dimanganese cluster (47) and many nonphysiological metal chelates (47)(48)(49)(50). We believe that none of these types of metal containing systems is the source of the observed 2,3-HPCD catalase activity for the following reasons: (i) the catalase activity requires nondenatured, holo-2,3-HPCD; (ii) the activity depends linearly on the amount of enzyme present; (iii) H 2 O 2 affects dioxygenase activity and HPCA affects catalase activity, both in a saturable manner; (iv) added iron and a variety of activated oxygen scavengers do not affect either dioxygenase or catalase activity; and (v) neither the steady state kinetics of the catalase activity nor the spectroscopic features of the 2,3-HPCD preparation are consistent with heme or dimanganese cluster containing catalases.…”
Section: Discussionmentioning
confidence: 99%
“…H3b5nsalpr (38.8 mg, 0.1 mmol) was dissolved in a mixture of acetonitrile (10 cm 3 ) and methanol (8 cm 3 X-ray quality crystals were grown by slow evaporation of the reaction solutions.…”
Section: [Co2(b5nsalpr)2(ch3oh)] (1)mentioning
confidence: 99%
“…1 The H3b5nsalpr ligand is a pentadentate ligand, having two phenolic-oxygen and two imino-nitrogen donor-atoms and one set of bridging alcohol-oxygen donor atom to give dinuclear manganese(II) 2 and manganese(III) 3 complexes with tridentate O,N,O-chelates. The ligand also forms a mononuclear copper(II) complex with a tetradentate O,N,N,O-chelate, when the central bridging alcohol-oxygen atom cannot be deprotonated.…”
mentioning
confidence: 99%